Are you a good mimic? Neuro-acoustic signatures for speech imitation ability - Reiterer, Susanne M.; Hu, Xiaochen; Sumathi, T. A.; Singh, Nandini C. (Frontiers in Psychology, 2013)
We investigated individual differences in speech imitation ability in late bilinguals using a neuro-acoustic approach. 138 German-English bilinguals matched on various behavioral measures were tested for “speech imitation ability” in a foreign language, Hindi, and categorised into “high ” and “low ability” groups. Brain activations and speech recordings were obtained from 26 participants from the two extreme groups as they performed a functional neuroimaging experiment which required them to “imitate“ sentences in three conditions: (A) German, (B) English and (C) German with fake English accent. We used recently developed novel acoustic analysis, namely the ‘articulation space’ as a metric to compare speech imitation abilities of the two groups. Across all three conditions, direct comparisons between the two groups, revealed brain activations (FWE corrected, p< 0.05) that were more widespread with significantly higher peak activity in the left supramarginal gyrus and postcentral areas for the low ability group. The high ability group, on the other hand showed significantly larger articulation space in all three conditions. In addition, articulation space also correlated positively with imitation ability (Pearson’s r=0.7, p<0.01). Our results suggest that an expanded articulation space for high ability individuals allows access to a larger repertoire of sounds, thereby providing skilled imitators greater flexibility in pronunciation and language learning.